Pelaksanaan Penilaian Diagnostik Non Kognitif di Sekolah Dasar - Trisna, Trisna; Anggelina, Selin Edri; Nazurty, Nazurty; Indryani, Indryani; Sastrawati, Eka (MODELING: Jurnal Program Studi PGMI, 2024)
The aim of the research carried out is to analyze how non-cognitive diagnostic assessments are carried out. This research uses descriptive analytical methods with a qualitative approach. The data collection techniques used were through observation, questionnaires and interviews. The research subjects were class V students at SDN 160/IV Jambi City with a total of 13 students. Meanwhile, data analysis is carried out through data reduction, data presentation and drawing conclusions. The results of the planning analysis obtained data that class V students at SDN 160/IV Jambi City had sufficient development or needed to be improved as evidenced by 23% or 3 out of 13 students having very good emotional development, 38% or 5 out of 13 students having emotional development which is good, 38% or 5 out of 13 students have sufficient emotions or need to be improved. The students' learning motivation is very good, as evidenced by 30% or 4 out of 13 students having very good learning motivation, 46% or 6 out of 13 students having good learning motivation, and 23% or 3 out of 13 students having sufficient learning motivation (necessary improved. Meanwhile, the learning styles of students tend to vary, namely 3 students have a visual learning style, 4 students have an auditory learning style, and 6 students have a kinesthetic learning style.